Sequential exploratory mixed-method research of an eHealth intervention on blood pressure, sleep quality and physical activity in obstructive sleep apnoea: rationale and methodology of the Moore4Medical trial protocol - Manuel Sánchez-de-la-Torre; Ferran Barbé; Oriol Martínez-Navarro; Francisco José Verdejo-Amengual; Fran Valenzuela-Pascual; Joan Blanco-Blanco; Rabie Adel El Arab; Esther Rubinat-Arnaldo; Maria Masbernat-Almenara; Francesc Rubí‑Carnacea; Blanca Manuel Martí (BMJ Open Respiratory Research, 2024)
Introduction The management of a chronic and frequent pathology, such as obstructive sleep apnoea (OSA), requires personalised programmes that implement new technology-based tools to improve the comprehensive treatment of the patient to reduce the morbidity associated with this disease. This study will evaluate the effectiveness of an eHealth tool in managing the pathophysiological consequences of OSA and how they impact the quality of life after 3 months of intervention among adults.Methods and analysis This is a mixed-method sequential exploratory study protocol. Participants will be≥18 years with a new diagnosis of moderate OSA and diagnosed with hypertension. The qualitative phase will consist of personal semistructured interviews. The quantitative phase will be a triple-blind randomised controlled trial. The experimental group (n=135) will receive an eHealth intervention using an electronic wrist device and a mobile application that will offer specific healthcare recommendations, physical activity indications and hygienic and dietary advice. These recommendations will be based on the information obtained in the qualitative phase. Those in the control group (n=135) will receive the usual educational materials from the sleep unit. The primary outcome will be blood pressure changes at 3 months. Secondary outcomes are subjective sleep quality, sleep apnoea-related parameters, daytime sleepiness, physical activity, empowerment and motivation for change, quality of life, anthropometry, cost–benefit and adherence.Ethics and dissemination Ethical approval for the study has been obtained from the Hospital Universitari Arnau de Vilanova (CEIC-2511). Results will be published in a peer-reviewed journal.Trial registration number ClinicalTrials.gov Identifier: NCT05380726.